Konstruksi Gender Dalam Bidang Pendidikan Pada Pola Asuh - Era Fazira; Nuriza Dora (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This paper aims to provide an understanding of the gender construction in the field of education on childcare patterns. The type of research used in this paper is qualitative with analytical descriptive methods. This research is quite interesting because it discusses gender related to education as well as patterns of caring, there is a lot of research on gender, but most of it deals from the point of view of household life and focuses on formal education. The results of the research show that in the field of education there are differences that are constructed socially based on the gender of the child through the pattern of parental care of the parents, these differences are nurture that has been cultivated in the community of the New Bangun Village of Sei Kepayang District of Asahan. Therefore, both the government and the educational institutions need to socialize on equal access to education for all genders and the application of appropriate custody patterns to children, so that parents can provide good foster care and provide urgent education to children.